Improvement of the institutional foundations of the development of public-private partnership in the service sector - Omonov Shermukhammad Bekmurodovich (Genius Journals, 2024)
In this article have been researched the features of the formation of the public-private partnership mechanism, the main goals of state policy, the main directions of economic activity between state and private business entities, the main advantages of participation in public-private partnership projects, the implementation of publicprivate partnership projects, public-private partnership the organizational structure of the private partnership development agency, the main forms of public-private partnership in the service sector, the directions of development of the system of interaction between the public and private sectors.
Keywords: Service sector; public sector; private sector